PEMBELAJARAN VCT MODEL CERITA TERHADAP MORAL DAN AGAMA ANAK 5-6 TAHUN TK ISLAM AKRAMUNNAS PEKANBARU - Putri Clawson; Mira Arianti (P3M STKIP 'Aisyiyah Riau, 2020)
The purpose of this study was to determine how much influence the learning of Value Clarification Technique (VCT) story models on moral and religious behavior of children aged 5-6 years in the Akramunnas Islamic Kindergarten, Pekanbaru. This research uses a quantitative approach and the type of research is experimental. Experimental research is research that provides treatment of research variables (independent variables), then observes the consequences of these treatments on research objects (dependent variables). The sample in this study were all early childhood in the Akramunnas Islamic Kindergarten in Pekanbaru, namely as many as 1 class, 24 of which were local children, B1 as the control class and B2 as the experimental class. The results of data analysis and discussion in this study can be concluded as follows: Moral and religious behavior of children aged 5-6 years at the Akramunnas Islamic Kindergarten Pekanbaru after being given treatment in the form of learning the value clarification technique (vct) story model has increased and is relatively high, meaning there is an effect of learning the value clarification technique (vct) story model on children's moral and religious behavior, when compared to before learning the value clarification technique (vct) story model. Learning value clarification technique (vct) story model has a positive influence of 62.84% on the moral and religious behavior of children aged 5-6 years at the TK Akramunnas Pekanbaru